Changing Disability Status and Changes in Health, Participation Restrictions and Activity Limitations in Denmark: Does the Choice of Measure Matter? - Anna Amilon; Mads Lybech Christensen (Scandinavian Journal of Disability Research)
Significant proportions of individuals respond inconsistently over time to disability questions in surveys. However, it is unclear why such changes in disability status arise. This study is the first to explore the prevalence and determinants of changes in disability status for two internationally recognized and widely used disability survey measures: the Washington Group Short Set on Functioning (WG-SS) and the Global Activity Limitation Indicator (GALI). We use Danish longitudinal survey data collected in 2016 and 2020 on 10,586 respondents aged 16–64 to systematically compare within-person changes in disability status. For both measures, changing disability status is more prevalent than consistent disability status. Moreover, changing disability status is associated with the corresponding changes in health, participation restrictions and activity limitations. Individuals with consistent disability status are in a more disadvantaged situation than individuals with changing disability status. Including questions about duration of disability in surveys may help identify respondents affected by accumulated disability-related disadvantage.